Attitudes towards poverty - Andrzej Derdziuk (The Person and the Challenges. The Journal of Theology, Education, Canon Law and Social Studies Inspired by Pope John Paul II)
Poverty, perceived as a lack of basic consumer goods, gives rise to a whole range of outcomes which affect not only the material dimension of human existence, but also influence social relations and references to spiritual values. Attitudes which could be associated with involuntary and unacceptable poverty include: doubt in the Divine Providence, bitterness, jealousy and envy, blaming others, lack of gratitude and in perceiving good, laziness, lack of initiative, escalating demands, gluttony and greed as well as meanness. However, joy, peace, freedom and solidarity with the poor, as well as work and enterprise, are symptoms of evangelical attitudes of the poor in spirit. Attitudes to poverty point to a wide range of human behaviours towards possessions and in effect, reveal an individual’s sense of value.